Case report: One case of umbilical vein thrombosis in the second trimester with associated portal vein thrombosis after childbirth - Dai, Wei-Wei; Hou, Qi-Shu; Yang, Lian-Hua; Chen, Shang-Qin; Ye, Ji-Feng (Frontiers in Medicine, 2023)
Background: Umbilical vein thrombosis is a rare pregnancy complication, that is difficult to detect prenatally but can lead to poor fetal outcomes. Case presentation: We described a 33-year-old primiparae who was identified as having umbilical vein thrombosis by ultrasound at 21 weeks gestation, and the neonate was found to have a portal vein thrombus after delivery. Following enoxaparin anticoagulant therapy, the thrombus disappeared within 3 weeks. No thrombus formation occured during the 10-month follow-up, and the baby was in excellent clinical condition. Conclusions: Umbilical cord anomalies, abnormal fetal coagulation function, intrauterine infection, and maternal diabetes may lead to the formation of umbilical cord thrombosis. Owing to the poor fetal outcomes related to umbilical thrombosis, pay attention to abnormal clinical signs during prenatal ultrasound, fetal heart monitoring and counting fetal movements can help in the early identification of umbilical cord thrombosis. Keywords: neonate; umbilical vein thrombosis; portal vein thrombosis